What are the challenges in taxing the informal economy and possible ways to overcome them? - Mbedu, Noluvuyo Bridgette (University of the Witwatersrand, Johannesburg, 2021)
Recent years have witnessed increased attention towards the challenges of taxing the informal economy (Joshi, Prichard & Heady 2012:1). However, this research report aimed to argue whether informal economy businesses in South Africa should be included in the tax system, given that the challenges of taxing the informal economy will need to be overcome. Other African countries such as Nigeria, Uganda, Cameroon and Ethiopia have attempted to tax the informal sector directly, and some businesses are bribing tax officers to reduce their company's tax payments. If the marginal bribe rate is lower than the statutory marginal tax rate, the company's tax payments will be reduced. (Kundt: 2017:6). Prichard (2012:16) has mentioned that the policy makers focus on the cost and benefits of taxing the informal economy. This research report also aimed to argue about the analysis that is needed to overcome the challenges of taxing the informal economy
A research report submitted in partial fulfilment of the requirements for the degree of Master of Commerce (specialising in taxation) to the Faculty of Commerce, Law, and Management, School of Accountancy, University of the Witwatersrand, Johannesburg, 2021
Keywords: UCTD; Informal sector; Taxation; Developing countries; Informal economy; Hard-to-tax; SDG-8: Decent work and economic growth